Peningkatan Literasi Sumber Daya Air Tanah Menggunakan Media Interaktif Berbasis Android - Sadewa Purba Sejati; Ifnu Rifki Nurhidayanto (Universitas Lancang Kuning, 2022)
Groundwater is one of the elements of the geosphere that plays an important role in achieving sustainable development. The decrease in the quantity and quality of groundwater is very likely to occur due to intensive anthropogenic dynamics which often ignore environmental rules. The neglect of environmental rules that have the potential to reduce the quantity and quality of groundwater resources is caused by a lack of literacy and knowledge of groundwater science. Literacy of groundwater resources needs to be applied to all levels of society, especially the younger generation as the successor of sustainable development so that groundwater sustainability is maintained. Literacy resources to increase insight need to contain visual elements, animations, descriptions and can be accessed by Android-based smart phones. The realization of solutions to partner problems will be realized through training, discussions, and questions and answers. The training activities were carried out to provide an understanding of how to download, install, and use the Groundwater App with a smartphone. Discussion and question and answer activities were carried out to discuss the visual and interactive substance presented by the application. The activities that have been carried out have been able to increase the insight of the younger generation about groundwater resources.